2020
DOI: 10.1039/c9sm01119f
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and flow in complex liquids

Abstract: Diffusion of a probe in complex liquids and length scale dependent viscosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…[63] and the general framework for viscosity of Ref. [64]. The results that we provide could form material for an in-depth comparison of PFT and MCT, possibly along the lines of Ref.…”
Section: Discussionmentioning
confidence: 54%
“…[63] and the general framework for viscosity of Ref. [64]. The results that we provide could form material for an in-depth comparison of PFT and MCT, possibly along the lines of Ref.…”
Section: Discussionmentioning
confidence: 54%
“…This might be reasonable in the limit of weak non-Newtonian effects, but may lead to imprecise conclusions for fluid mediums exhibiting strong non-Newtonian behaviour, as the Stokes-Einstein equation fails in describing diffusion in complex media. Recently, Makuch et al (2020) devised a relationship between translational and rotational diffusion coefficients which depends on the size of solute. Such theoretical formulation can provide a database for a precise description of diffusion in various complex fluids.…”
Section: Discussionmentioning
confidence: 99%
“…We also assume the solute molecules, inside and outside the interaction layer, to follow Fickian diffusion with constant diffusivity. It has been reported that the presence of polymers significantly affects the diffusive mass transport in a stagnant polymeric medium (Maldonado-Camargo & Rinaldi 2016; Makuch et al 2020). To our knowledge, there has been no study conducted on the mass transport in sheared complex flows.…”
Section: Active Particle In a Second-order Fluidmentioning
confidence: 99%
“…For small tracer particles with λ < 1, however, the tracer particles are significantly affected by the molecular nature of the polymer molecules and the Stokes-Einstein relation ( 36) breaks down [42][43][44]. Physically, the tracer particles experience a reduced effective viscosity η e within the pore space that is smaller than the macroscopic viscosity η [15,45,46]. Figure 4 shows D 22 calculated from (36) with equation ( 15) for the PEG viscosity (dotted curves), along with experimental data for three polymer molecular weights (PEG 200, λ = 0.44; PEG 400, λ = 0.30; and PEG 2000, λ = 0.13).…”
Section: Breakdown Of the Stokes-einstein Equationmentioning
confidence: 99%